PENERIMAAN TEKNOLOGI TELEMEDICINE DI INDONESIA: ANALISIS FRAMEWORK TAM2 - Nurlita Wahyu Aziza; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The persistence of unmet healthcare service needs in Indonesia underscores the importance of telemedicine as an alternative mode of healthcare delivery. Adoption gap shown through generally positive public sentiment towards telemedicine but relatively low actual usage rates. This study examines the acceptance of telemedicine services using the Technology Acceptance Model 2 (TAM2). A quantitative research design was employed, online survey conducted of 248 respondents who had prior experience using telemedicine applications in Indonesia. Purposive sampling was applied, and the data analyzed using Partial Least Squares (PLS). It was found that perceived usefulness, perceived ease of use, and social influence significantly affect users’ intention to use telemedicine, which in turn influences actual usage behavior. This study highlights the role of social influence as societal pressure in shaping telemedicine acceptance which an aspect that remains underexplored in the Indonesian literature.